Three new species of Marphysa Quatrefages, 1865 (Polychaeta: Eunicida: Eunicidae) from the south coast of China and redescription of Marphysa sinensis Monro, 1934 - Liu, Yubin; Hutchings, Pat; Sun, Shichun (Zootaxa, 2017)
Three new species of Marphysa Quatrefages, 1865 (Polychaeta: Eunicida: Eunicidae) are described from the south coast of China, M. tripectinata n. sp., M. multipectinata n. sp. and M. tribranchiata n. sp. with comments on the usefulness of pectinate chaetae to separate species. Marphysa sinensis Monro, 1934 is redescribed with a lectotype designated. The genus Marphysa is widely collected for bait and export for recreational fishermen and anglers in China and yet the number of species involved and their native distribution is currently unknown. Such information is critical for aquaculture programs which are rearing these species.